ESTABLISHMENT OF PERMANENT SAMPLE PLOT NETWORK FOR MONITORING THE STRUCTURE AND GROWTH OF LOGGED-OVER FORESTS IN SARAWAK, MALAYSIA - Bibian, Diway; YIING, LING CHEA; Yayoi, Takeuchi; Mohd Effendi, Wasli (Forestry Department Peninsular Malaysia, 2023)
The establishment of a permanent sample plot (PSP) network in Sarawak is to collect scientific data on tree growth, forest structure and species composition from logged-over forest areas particularly the forest management unit (FMU). Scientific data provide evidence on changes in the forest over a period of time due to harvesting operation. Additionally, the PSP data when combined with all forest assessment data is important to generate tree growth and yield model for projection of the annual allowable cut. A total of 23 permanent sample plots of 1 ha were established and assessed between 2016 and 2019 at selected FMU areas within coupes of different ages after the last harvesting. All trees with 10 cm diameter at breast height (DBH) and above were measured. Data recorded include DBH, tree height, stand form and the location of the tree in the field. Plant specimens were collected for species identification and a database was constructed. A total of 13,626 trees were measured from all plots represented by at least 864 species of trees. The mean density of trees ranged from 468 to 660 trees/ha. Tree density was generally lower compared to unlogged area in Batang Ai National Park. Species composition varied between FMU areas as influenced by the age of the forest after logging and forest types. Recovery of the forest after logging was evaluated using pioneer and mature species along the aged forests. The abundance of pioneer species and regenerating of mature species was reflected by the intensity of the forest disturbances. However, the PSP data was not enough to conclude if the forest is sustainable for timber production within 25 years. Hence, a long-term monitoring is essential.